Comparative side-effects of adapalene and benzoyl peroxide combination gel with Adapalene monotherapy and Benzoylperoxide monotherapy in the treatment of Acne vulgaris - Islam, KA; Akhtar, N; Shahidullah, M; Khondker, L; Khan, MSI (Community Based Medical Journal, 2013)
A controlled clinical trial was conducted in the department of Dermatology and Venereology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh to compare the side-effects of adapalene and benzoyl peroxide combination gel with adapalene monotherapy and benzoyl peroxide monotherapy in the treatment of acne vulgaris. The study conducted in sixty patients. Group A (case) 20 patients were treated with adapalene and benzoyl peroxide combination gel, group B (control) 20 patients were treated with topical adapalene and group C (control) 20 patients were treated with topical benzoyl peroxide. The side effects experienced by patients of different groups in their first follow up were noticed. In group A - erythema, scaling, dryness, burning and pruritus were present in 45%, 10%, 35%, 40% and 10% of patients and in group B, 35%, 25%, 30%, 35% and 15% respectively. However in group C dryness and pruritus were absent in all the patients and the erythema, scaling and burning were 30%, 25% and 25% respectively. In 5th follow-up visit, in group A- erythema, scaling, dryness and pruritus were present in 15%, 5%, 15%, and 5% of patients respectively and burning was absent in group A. In group B erythema, scaling, dryness, and pruritus were 15%, 5%, 5% and 5% and burning was absent in group B. However in group C scaling, burning, dryness and pruritus were absent in all the patients. Erythema was present in 10% cases in 5th follow-up visit. It was evidenced in the present study that the overall adverse effect is slightly higher with the adapalene- benzoyl peroxide combination therapy in relation to the adapalene and benzoyl peroxide (BPO) monotherapies in the treatment of acne vulgaris. DOI: http://dx.doi.org/10.3329/cbmj.v2i2.16699 Community Based Medical Journal 2013 July: Vol.02 No 02: 52-56